Students’ Literacy, Numeracy, and Problem Solving Profile on Salt Hydrolysis - Salma Hafizhah Az-Zahra; Wiwi Siswaningsih; Nahadi (Jurnal Pendidikan dan Pembelajaran Kimia, 2026)
This study profiled eleventh-grade students' reading literacy, numeracy, and problem-solving competencies using a Minimum Competency Assessment (MCA) instrument on salt hydrolysis contextualized within SDG 6 (clean water and sanitation). The instrument, developed following an established framework for competency-based assessment design and judged content-valid by seven expert validators, comprised 24 items (17 reading-literacy, 7 numeracy) built around five SDG 6-themed stimulus texts, with problem-solving items mapped onto four aspects of engineering problem-solving. Responses from 34 students were analyzed descriptively using a standard MCA competency-level framework and percentage-based categorization. Students reached a Proficient aggregate level in both reading literacy (index 1.897) and numeracy (index 1.839), although numeracy was concentrated at the Basic level for 44.1% of students, revealing a gap between the aggregate index and the modal student experience. Across both groupings, Planning a Solution was consistently the weakest problem-solving aspect at every competency level, including among the most proficient students. Strong reading-literacy or numeracy performance does not straightforwardly translate into systematic, quantitatively grounded solution planning, indicating a structural gap that instruction on salt hydrolysis within an SDG 6 context should explicitly target.